2021
DOI: 10.26434/chemrxiv-2021-z44z2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Site-specific nonenzymatic peptide S/O–glutamylation reveals the extent of substrate promiscuity in glutamate elimination domains

Abstract: Formation of dehydroalanine and dehydrobutyrine residues via tRNA-dependent dehydration of serine and threonine is a key post-translational modification in the biosynthesis of lanthipeptides and thiopeptides. The dehydration process involves two reactions, wherein the O–glutamyl Ser/Thr intermediate, accessed by a dedicated enzyme utilizing Glu-tRNAGlu as the acyl donor, is recognized by the second enzyme, referred to as the glutamate elimination domain (ED), which catalyses the eponymous reaction yielding a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Chemical structure assignments of the resulting products were guided by mass shifts, HPLC retention times, and the available substrate specificity data for Laz enzymes (Supporting Information S2.5). 34,45,46 All tested precursors underwent efficient maturation to thiopeptides as judged by the formation of leader-NH 2 , which was the major reaction product in every case (Figure 2c). Modification of 11 constructs yielded a single major thiopeptide product, despite the presence of potentially modifiable Ser/Thr/Cys residues in the random regions of 13 peptides.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…Chemical structure assignments of the resulting products were guided by mass shifts, HPLC retention times, and the available substrate specificity data for Laz enzymes (Supporting Information S2.5). 34,45,46 All tested precursors underwent efficient maturation to thiopeptides as judged by the formation of leader-NH 2 , which was the major reaction product in every case (Figure 2c). Modification of 11 constructs yielded a single major thiopeptide product, despite the presence of potentially modifiable Ser/Thr/Cys residues in the random regions of 13 peptides.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…In the second step, the elimination domain (LazF) catalyzes a retro-Michael reaction in the Ser(OGlu) intermediate to yield the Dhacontaining product. 56 Although preliminary enzyme characterization indicated that LazBF prefers a Trp residue in position +1…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In the second step, the elimination domain (LazF) catalyzes a retro-Michael reaction in the Ser(OGlu) intermediate to yield the Dha-containing product. 56 Although preliminary enzyme characterization indicated that LazBF prefers a Trp residue in position +1 relative to the modification site, the enzyme also displayed more elaborate preferences which eluded generalization. 47,53 Here, we have sought to develop an mRNA display/deep learning-based platform for comprehensive profiling of LazBF substrate fitness landscapes.…”
Section: Development Of the Mrna Display Scheme For Lazbf Profilingmentioning
confidence: 99%